Public disclosure as a communication approach for enhancing compliance of industries with water quality standards in Laguna de Bay - Cabral-Castillo, Hermilea Marie P. (The Philippine Journal of Development Communication, 2010)
This study sought to: 1) describe the socio-technical profiles of selected case-industries subjected to the Laguna de Bay Region-Public Disclosure Program (LDBR-PDP); 2) determine the industries' level of understanding, perception, and attitude toward public disclosure as a communication approach to enhance compliance with anti-pollution law; 3) discuss the positive and negative aspects associated with LDBR-PDP as a communication approach for compliance; and 4) draw out suggestions for improvement of public disclosure as a communication approach for enhancing industries' compliance with water quality standards in Laguna de Bay. Descriptive statistics was used to analyze data. Weighted means were computed for the perception and attitude responses of the industries. Of the 103 industries considered for this study, only 62 industries were successfully contacted. Only 10 questionnaires were sent back. The low turnout could have implications on the program's administrative aspects. Of the 10 industrial respondents, majority had blue ratings, two had black ratings, and one was rated red. Four of these industries also participated in the first LDBR-PDP. Despite low turnout of respondents, results of the study are indicative of the industries' response to the program. Results were solely based on PCO's understanding, attitude toward, and perceptions of the program, as representatives of the industries. On the average, respondents had a moderate level understanding of the program, it's processes and procedures. Results also indicate that their level of understanding does not have a bearing on their color, hence, compliance ratings. This implies that a high or low level of understanding does not necessarily translate to good or bad performance in terms of compliance. Industries mostly had favorable perceptions specifically of credibility and competence of implementors, accuracy of instruments, and transparency and fairness of procedures. Favorable perceptions do not necessarily translate to good compliance ratings/color rating. In fact, in some cases, negative perception about a few aspects was affected somehow by ratings. Overall, all industries had a positive attitude toward LDBR-PDP showing that despite differences in compliance ratings, the industries, whether compliant or non-compliant, still regarded LDBR-PDP favorably. Positive aspects cited by the industries were: "emotionally"/social rewards; recognition/rewards boosting image of the industry; and awareness-raising regarding environmental performance of the industry. Negative aspects can be categorized as operational/implementation problems and negative impacts for red- or black-rated companies. Comments were generally about suggestions for improving the implementation of the program - LLDA's management of the program, it's process and procedures, and about PDP as a communication approach.